丑小鸭 ebook The ugly duckling. - Andersen, Hans Christian (Firefly Picture Books: Bilingual Classic Fairy Stories., 2015)
Created by domestic top painters especially for the books, annotation of the classic fairy tales collected works with splendid pictures. Chinese-English bilingual description, in which Chinese vivid and vigorous, and English terse and briefly. 国内顶级绘本画家量身打造，运用美轮美奂的绘本诠释世界经典童话全集。